The impact intervention of handling obstetric case using Oprocot model - Agus Sulistyono, - (Foundation for Environtmental Protection and Research, 2020)
OPROCOT (Out of the box, Proactive, Comprehensive, Top-Down) model developed by Task Force for MMR has been applied to Syarifah Ambami Rato Ebu (SARE) Hospital, Bangkalan, Indonesia since 2015. From 42 items intervention, mentoring and involvement as an affiliated hospital are the main interventions. We evaluated the interventions results and analyzed the impact of OPROCOT model to the performance of department of obstetrics and gynecology. Descriptive and observational study from medical records of SARE General Hospital was conducted from January 2014 to December 2016. There was an exponential increase in the number of obstetric patients as follows: 2014: 1024 cases, 2015: 1299 cases, and 2016: 1782 cases. More specifically, in eclampsia: 23 cases in 2014 increased to 60 cases in 2015 and 89 cases in 2016. Also, severe preeclampsia from 131 cases in 2014 increased to 191 cases in 2015 and 235 in 2016. For operative vaginal deliveries, in 2014 there were no cases, in 2015 there were 11 cases, in 2016 there were 25 cases. Referred cases decreased as follow, in 2014: 74 cases, 2015: 25 cases, and in 2016: 6 cases. Mentoring and involvement of affiliated hospital increased obstetric performance and reduced referred patients.